Article Survey Kepuasan Pelayanan Kesehatan Masyarakat Di Kota Malang: Jurnal Administrasi Publik: - Erlambang, Nanda; Rizki Fillya Curtinawati, Rizki Fillya Curtinawati (Publiciana, 2024)
ABSTRACT Health is a fundamental right and needs that humans need to live their lives. As social creatures, humans cannot live alone to guarantee that their right to health can be fulfilled, therefore, in the modern world of life, the state plays a role in providing access to health for the entire community. In Malang City, to be precise, the Dinoyo Community Health Center (Puskesmas) is a model community health center that is quite good at implementing preventive health access to the community by prioritizing the program (PTSSIBE), namely professionalism, responsibility, quality awareness, time awareness, initiative, cleanliness, empathy. The cultural innovation of health services with this program certainly provides high standards for the community, so the Dinoyo Malang Community Health Center is trusted to open Sexually Transmitted Infection (STI) clinic services. From the health service program and achievements obtained by the Dinoyo Malang Community Health Center, a community satisfaction survey can be described using indicators of requirements, procedures, service time, costs/tariffs, service results, implementer competence, implementer behavior, service announcements, complaints about handling critical suggestions. The community satisfaction survey aims to evaluate the advantages and disadvantages of the health service innovation program (PTSSIBE) at the Dinoyo Community Health Center, Malang City. This research uses a quantitative descriptive method with four alternative measurement scales for community responses, namely: strongly agree (SS: score 4), agree (S: score 3), disagree (ts: score 2), and strongly disagree (sts: score 1 ). The results of the research show that out of 100 respondents (the public) gave an assessment of satisfaction with health services at the Dinoyo Malang Community Health Center as follows: the competence and professionalism of the implementers received the best assessment from the community with a score of 3.00, the behavior of the implementers received a score of 2.93 and service announcements with a score of 2.92. The health service survey results with the lowest scores were complaints, criticism, and suggestions with a score of 2.60, service time with a score: 2.74, and service costs with a score of 2.76. It can be concluded that according to the results of the public health service satisfaction survey at the Dinoyo Community Health Center, Malang City, it is necessary to carry out a program evaluation (PTSSIE) to improve the quality of health services. Keywords: Satisfaction Survey, Health Services, Malang City.